1979
DOI: 10.1002/app.1979.070240417
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic mechanical properties of poly(p-phenyleneterephthalamide) fiber

Abstract: SynopsisThe dynamic mechanical properties of poly@-phenyleneterephthalamide) fiber were investigated.Measurements of the dynamic mechanical properties were carried out on samples of low crystallinity and low orientation over a temperature range from -100 to +50O0C at a frequency of 110 Hz, at a heating rate of SoC/rnin. Five relaxation processes were revealed a t -30,60,170, 27OoC, and in the vicinity of 46OoC, respectively. The prominent dispersion peaks located at -30,60, and 46OOCwere termed the 7 , p, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 2 publications
0
22
0
Order By: Relevance
“…In this study, we focus on Kevlar 49, a highermodulus grade of Kevlar designed for load-bearing applications in cables, cloth, and aerospace components [1]. While many studies of the quasi-static behavior of the various types of Kevlar fiber are available [2], there have been far fewer investigations on their dynamic mechanical properties [3]. Those that do exist characterize the storage and loss modulus as a function of temperature without considering the effects of continuously increasing strains, mainly due to the limitations of current dynamic mechanical analysis (DMA) [3].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, we focus on Kevlar 49, a highermodulus grade of Kevlar designed for load-bearing applications in cables, cloth, and aerospace components [1]. While many studies of the quasi-static behavior of the various types of Kevlar fiber are available [2], there have been far fewer investigations on their dynamic mechanical properties [3]. Those that do exist characterize the storage and loss modulus as a function of temperature without considering the effects of continuously increasing strains, mainly due to the limitations of current dynamic mechanical analysis (DMA) [3].…”
Section: Introductionmentioning
confidence: 99%
“…While many studies of the quasi-static behavior of the various types of Kevlar fiber are available [2], there have been far fewer investigations on their dynamic mechanical properties [3]. Those that do exist characterize the storage and loss modulus as a function of temperature without considering the effects of continuously increasing strains, mainly due to the limitations of current dynamic mechanical analysis (DMA) [3]. DMA tests can only be carried out at low harmonic displacements to ensure linear viscoelasticity, severely limiting the ability to characterize the viscoelastic response of materials past their yield point [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…18.6 GPa and a tensile strength of 0.6 GPa. Ito The ZD/ZA method has already been applied et al 2 reported that high-molecular weight PET to many polymers, such as poly(ethylene terephfibers were treated using a multistep draw techthalate) (PET), 4,5 i-polypropylene, 6,7 nylon 6, 8,9 nique, and that the tensile modulus and strength nylon 66, 10 nylon 46, 11 poly(vinyl alcohol), 12 and of resultant drawn fibers reached 39 and 2.3 GPa, poly(ether ether ketone) 13 fibers to improve their respectively. We used a zone-drawing/zone-anmechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Five relaxation transitions at temperatures of 30 (7), 60([3), 170([3"), 270(~*), 460(ot)~ [ 16], according to other data at 140, 260, and 460-540~ [I7], are -known for PPTA. With the appearance of segmental mobility of the macromolecules at a temperature above 460~ their crystallization is accelerated in intercrystalline regions and the crystal structure of the polymer is completed.…”
Section: H2n~nh2mentioning
confidence: 99%